Revisiting faculty members' goals for the undergraduate chemistry laboratory. Issue 1 (18th October 2022) - Connor, Megan C.; Rocabado, Guizella A.; Raker, Jeffrey R.
Abstract : Over a decade has passed since faculty members' goals for the undergraduate chemistry instructional laboratory were first investigated on a large, national scale in the United States. This study revisits these goals, using data from a 2022 national survey of chemistry faculty members in the United States ( n = 521) to investigate current objectives, including how those goals vary with course, institutional context, and receipt of funding for improving undergraduate chemistry courses. A modified version of the Faculty Goals for Undergraduate Chemistry Laboratory Instrument was used to measure goals, with psychometric evidence providing support for its use across the studied contexts, with the exception of the general chemistry laboratory. Goals were associated with course and receipt of funding but not institution type, both with regard to institutions' highest chemistry degree awarded and approval from the American Chemical Society to award certified bachelor's chemistry degrees. Results suggest that faculty members may adopt a distinct set of goals not immediately associated with the practice of chemistry in the general chemistry laboratory. Further, goals increasingly focus on providing research experience and cultivating disciplinary knowledge and skills with progression through the chemistry curriculum; this focus increases more abruptly when moving from large-enrollment lower-level courses to small-enrollment upper-level courses. Findings imply a need for increased efforts focused on (1) evaluating goals for the general chemistry laboratory, including whether those goals contribute to overarching curricular objectives, (2) promoting adoption of evidence-based pedagogies in large-enrollment contexts to better align instruction with the practice of chemistry, (3) supporting faculty members in procuring funding to improve courses, and (4) refining professional societies' evaluation criteria for undergraduate chemistry programs.